POSYANDU INFORMATION SYSTEM USING BORLAND DELPHI 7 AT POSYANDU SETIA WARGI MARGAHURIP - Rosmalina Rosmalina; Yaya Suharya; Muhammad Fahri Fauzi (Universitas Sangga Buana, 2021)
Posyandu Setia Wargi Margahurip is a non-governmental activity that aims to maintain public health, especially for toddlers. Until now, data recording at the Setia Wargi Margahurip Posyandu is still manual, that data and information processing is still experiencing many obstacles, especially in terms of effectiveness. The development of technology and information that is growing rapidly in this era of globalization causes all fields in human life to involve technology to facilitate human work in various fields. Therefore, the idea emerged to create a desktop-based Posyandu information system design to facilitate data processing services at the Posyandu. This Posyandu information system was build using Borland Delphi 7 with Microsoft Access as the database. The Posyandu information system development method uses the SDLC (Software Development Life Cycle) method with the Waterfall Model and problem analysis using the PIECES method. The result of this research is a desktop-based Posyandu information system application that can help Posyandu cadres and Posyandu health workers Setia Wargi Margahurip in facilitating the process of data processing, searching, reporting, data storage